PROSES PEMBENTUKAN UNDANG-UNDANG MENURUT UU NO. 12 TAHUN 2011 TENTANG PEMBENTUKAN PERATURAN PERUNDANG-UNDANGAN - Dermina Dalimunthe (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2018)
The establishment of laws according to Law No. 12 of 2011 covers the stages of planning, drafting, discussing, ratifying and promulgating. The process of forming uu in Law NO. 12 of 2011 has new things, among others, the bill originating from the DPR, the President and the DPD must be accompanied by an academic draft bill, after the decision of MK No. 92 of 2012 the DPD participated in the deliberation of the bill on the level II although it did not reach the stage of decision making.The establishment of laws according to Law No. 12 of 2011 covers the stages of planning, drafting, discussing, ratifying and promulgating. The process of forming uu in Law NO. 12 of 2011 has new things, among others, the bill originating from the DPR, the President and the DPD must be accompanied by an academic draft bill, after the decision of MK No. 92 of 2012 the DPD participated in the deliberation of the bill on the level II although it did not reach the stage of decision making.